Draft genome sequence of Mycobacterium bovis 04-303, a highly virulent strain from Argentina - Nishibe, Christiane; Canevari Castelão, Ana Beatriz; Dalla Costa, Ricardo; Pinto, Beatriz Jeronimo; Varuzza, Leonardo; Cataldi, Angel Adrian; Bernardelli, Amelia; Bigi, Fabiana; Blanco, Federico Carlos; Zumarraga, Martin Jose; Almeida, Nalvo Franco; Araujo, Flabio Ribeiro de (American Society for Microbiology, 2020)
Mycobacterium bovis strain 04-303 was isolated from a wild boar living in a free-ranging field in Argentina. This work reports the draft genome sequence of this highly virulent strain and the genomic comparison of its major virulence-related genes with those of M. bovis strain AF2122/97 and Mycobacterium tuberculosis strain H37Rv.